The impact of the COVID-19 pandemic on university education in the field of construction: adaptations and challenges in the entrepreneurial training of students - Chasciar, Denisa Ramona; Coman, Claudiu; Vasile, Chasciar; Netedu, Adrian; Bularca, Maria Cristina; Toderici, Ovidiu Florin; Plescan, Costel; Anton, Mihail; Shields, Roxana; Plescan, Elena; Mardache, Andreea (Frontiers in Education, 2025)
This research analyzes the impact of the COVID-19 pandemic on university education in the field of construction, with a focus on the necessary adaptations and challenges encountered in the entrepreneurial training of students. The study was carried out on a sample of 318 students from the construction specializations of the Transilvania University of Brașov, and aimed to identify the changes induced by the global pandemic in educational activities, with a special focus on entrepreneurship activities. The results of the research suggest that the pandemic has led to a significant transition to online education, with a decrease in direct interaction between students and teachers and an increase in course theorizing. Also, the difficulties encountered by students in developing entrepreneurial skills were influenced by the availability of educational resources and the support provided by the university. The study also confirms the importance of online activities, such as conferences and mentoring courses in the field of entrepreneurship, as effective forms of support during the pandemic. Finally, the research proposes suggestions for improving entrepreneurial training within construction education, taking into account the needs and preferences expressed by students.